1996
DOI: 10.1038/nbt1096-1269
|View full text |Cite
|
Sign up to set email alerts
|

Stability of food allergens to digestion in vitro

Abstract: An integral part of the safety assessment of genetically modified plants is consideration of possible human health effects, especially food allergy. Prospective testing for allergenicity of proteins obtained from sources with no prior history of causing allergy has been difficult because of the absence of valid methods and models. Food allergens may share physicochemical properties that distinguish them from nonallergens, properties that may be used as a tool to predict the inherent allergenicity of proteins n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
637
1
21

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 826 publications
(685 citation statements)
references
References 23 publications
26
637
1
21
Order By: Relevance
“…As expected, both proteins were very resistant to pepsinolysis (data not shown) because ␤-LG is a poor substrate for pepsin [27][28][29][30]. Nevertheless, the duodenal digestion (trypsin and chymotrypsin) of the native and glycated ␤-LG gave rise to a very complex mixture of peptides after 1 h of incubation as was previously observed by reversed-phase LC-UV [13].…”
Section: Identification Of ␤-Lg Peptides Resulting From the In Vitrosupporting
confidence: 79%
“…As expected, both proteins were very resistant to pepsinolysis (data not shown) because ␤-LG is a poor substrate for pepsin [27][28][29][30]. Nevertheless, the duodenal digestion (trypsin and chymotrypsin) of the native and glycated ␤-LG gave rise to a very complex mixture of peptides after 1 h of incubation as was previously observed by reversed-phase LC-UV [13].…”
Section: Identification Of ␤-Lg Peptides Resulting From the In Vitrosupporting
confidence: 79%
“…It is a 65-kDa glycoprotein with an acidic isoelectric point. It is an abundant protein in the peanut (11) that survives food-processing methods intact (6) and is stable up to 1 h within the in vitro digestion systems designed to mimic the gastrointestinal tract (6). Resistance of allergens to digestive enzymes have been attributed to various factors including protease inhibitors or nonprotein components present in the extracts analyzed (7,24), direct effects on the secretion of endogenous proteins and/or the structure of the allergen itself (25).…”
Section: Discussionmentioning
confidence: 99%
“…glycoproteins (Ͻ70 kDa) with acidic isoelectric points that are highly abundant in food. These proteins are usually resistant to proteases, heat, and denaturants, allowing them to resist degradation during food preparation and digestion (6,7). Several studies have shown that the most allergenic portion of the peanut is the protein fraction of the cotyledon (8)(9)(10).…”
mentioning
confidence: 99%
“…The digestibility of protein causes another concern in respect of risk of allergenicity. Astwood et al 2) suggested that stability to pepsin digestion is a significant and valid parameter that distinguishes food allergens from non-allergens. In this study, the protein quality of red kidney bean, one of the representative varieties of common beans in Japan, was assessed by in vitro pepsin digestion.…”
mentioning
confidence: 99%
“…The protein concentration of the extracts was estimated by the micro assay procedure for a protein assay reagent (BioRad, Tokyo). The in vitro pepsin digestibility of intact flour and the heat-processed paste was examined by the method of Astwood et al 2) Intermolecular and intramolecular disulfide bonds were analyzed by nonreducing/reducing two-dimensional electrophoresis. Bean flour (200 mg) was mixed with 2 ml of extraction buffer (30 mM Tris-HCl, pH 7.9) containing 1 mM phenylmethanesulphonyl fluoride (PMSF) and 0.02% NaN 3 , then centrifuged at 10;000 Â g for 15 min.…”
mentioning
confidence: 99%